2015
DOI: 10.1074/jbc.m115.673046
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Peroxisome Proliferator-activated Receptor (PPAR)γ Agonist 2-Hydroxyethyl 5-chloro-4,5-didehydrojasmonate Exerts Anti-Inflammatory Effects in Colitis

Abstract: Background: A newly synthesized 2-hydroxyethyl 5-chloro-4,5-didehydrojasmonate (J11-Cl) has anti-inflammatory effects in carrageenan-induced paw edema. Results: J11-Cl ameliorates colitis through activation of PPAR␥ and modulation of NF-B and MAPK signaling. Conclusion: J11-Cl acts as an effective anti-inflammatory agent. Significance: A PPAR␥ agonist is a novel candidate to treat inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…On the basis of its structural similarity to that of 15d-PGJ 2 , methyl jasmonate (J-11) was investigated for SIRT activity, and its functional mechanisms of regulation of cancer cell death pathways were investigated. A previous study indicated that an α-haloenone analog, J7, exhibited enhanced in vitro anti-inflammatory potency ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of its structural similarity to that of 15d-PGJ 2 , methyl jasmonate (J-11) was investigated for SIRT activity, and its functional mechanisms of regulation of cancer cell death pathways were investigated. A previous study indicated that an α-haloenone analog, J7, exhibited enhanced in vitro anti-inflammatory potency ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impaired regulatory function after knockout of PPAR‐ γ in B cells was not due to reduced naive splenic CD5 + CD1d hi Breg cell generation, but instead to the activation‐induced IL‐10 + CD5 + CD1d hi Breg cell expansion. Our group and other groups recently described that nuclear factor‐ κ B and nuclear factor of activated T‐cell signal inhibition, which had been observed after PPAR‐ γ activation in effector cells, could dampen Breg cell activation . We cannot exclude the possibility that paradoxical effects of PPAR‐ γ activation on Breg cells initiated by a different immune balance might sometimes occur during immune responses.…”
Section: Discussionmentioning
confidence: 86%
“…Both natural and synthesized ligands such as rosiglitazone can bind to PPAR‐ γ . PPAR‐ γ activation was first noted to treat diabetes; its additional anti‐inflammatory and immunosuppressive functions were recently demonstrated through its ability to ameliorate CHS, EAE, arthritis etc . Whole‐body PPAR‐ γ +/− mice were more susceptible to autoimmune and inflammatory diseases such as immune arthritis and EAE, which further indicated that endogenous PPAR‐ γ activation also limited inflammation and immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…PPAR-γ reduces the expression levels of pro-inflammatory chemokines, including chemokine (C-C motif) ligand 20, CXC ligand (CXCL)2, CXCL3 and chemokine (C-X3-C motif) ligand 1 (CX3CL1) in colon tissues. It has been shown that increasing the transcriptional activity of PPAR-γ can modulate inflammatory signaling pathways, suggesting a novel target for therapeutic agents ( 117 ). The investigation of inflammatory markers in vascular disorders reveals augmented levels of circulating cytokines and chemokines among carriers of classic risk factors for atherosclerosis.…”
Section: Potential Role Of Ppar Agonists In the Treatment Of Cabmentioning
confidence: 99%